Institutional strengthening in village ecotourism development - Suhendri; Helena, Dida; Pahrudin (Universitas Islam Malang, 2023)
This study aims to explore village institutions in managing the tangkas lake ecotourism in Muaro Jambi Regency, Jambi Province. This research is based on ecotourism, which is being studied by many researchers as responsible tourism towards socio-economic and environmental sustainability. In addition, institutions in ecotourism management that should be oriented towards the people's economy are often confronted with the interests of a few people. Therefore, based on the objectives of this study, a qualitative method was used with a descriptive exploratory approach to obtain an overview of the findings to answer the research questions. While the primary research data obtained through observation, interviews, and documentation. Then the secondary data will go through a review of documents, literature, social media, or others according to the research objectives. The results of the study show that leadership and coordination have been developed quite well, which were initiated directly by the village government. Partnerships that are built in complementary synergies so that they become the basis for developing potential based on academic knowledge. Meanwhile, Lake Tangkas ecotourism promotion facilities have utilized social media with websites and Facebook to Instagram. However, the village government is too structurally involved with policy makers ranging from the village head to the village secretary, while the strategic position of the community can be more dominant. The university carries out dharma service but does not significantly influence the development and contribution of the tangkas lake ecotourism management institution.